Reconstructing The Function of Supreme Court Circular Letters As Internal Policy Regulations To Strengthen Judicial Supervision And The Uniformity of Judicial Practice - Muhotim; Aan Eko Widiarto; Dhia Al Uyun (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the reconstruction of the function of Supreme Court Circular Letters (Surat Edaran Mahkamah Agung/SEMA) as internal policy regulations in strengthening judicial supervision and promoting the uniformity of judicial practice in Indonesia. The issue arises because, although SEMA is widely applied by judges as an authoritative guideline in judicial practice, it is not formally included within the hierarchy of Indonesian legislation under Law Number 12 of 2011 concerning the Formation of Laws and Regulations. This condition has generated uncertainty regarding its legal status, binding force, and constitutional function within the Indonesian legal system. Accordingly, this research aims to analyze the binding force and legal function of SEMA as an internal policy regulation and to formulate a reconstruction model capable of enhancing its effectiveness in judicial supervision while maintaining consistency with the principles of the rule of law and judicial independence. This study employs normative legal research using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively through grammatical, systematic, and teleological methods of interpretation. The analysis is supported by the theory of the hierarchy of legal norms, the doctrine of internal policy regulations (beleidsregel), and the theory of judicial law-finding (rechtsvinding). The findings demonstrate that SEMA is not a statutory regulation but an internal policy instrument whose binding force derives from the Supreme Court's constitutional authority, statutory regulatory powers, and institutional acceptance within the judiciary. Furthermore, the reconstruction of SEMA should emphasize normative clarification, institutional strengthening, and operational improvement to reinforce its function as an internal policy regulation. Such reconstruction is expected to enhance judicial supervision, promote greater uniformity in judicial practice, and strengthen legal certainty without compromising judicial independence or the hierarchy of legal norms. The novelty of this study lies in proposing a comprehensive reconstruction model that clearly distinguishes SEMA as an internal policy regulation rather than a quasi-legislative instrument. The model integrates normative clarification, participatory institutional drafting, and operational evaluation, contributing to legal theory and judicial governance.